Pengaruh Disiplin Kerja Dan Llingkungan Kerja Tehadap Kinerja Karyawan Pada Perusahaan PT Semen Tonasa Kabupaten Pangkep - Nur Anisa; Nurdin Latif; Nurmega Nurmega (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This research aims to determine the influence of work discipline and work environment on employee performance at the company PT. Semen Tonasa District. Pangkep. The method used in this research is a quantitative method with the number of respondents being 75 employees who were used as samples using a sampling technique, namely using a saturated sample. The analysis used in this research is a multiple linear regression test. The results of simultaneous testing of work discipline and work environment variables have a positive and significant influence on employee performance variables as proven based on simultaneous test results with a significance value of f<α (0.000<0.05). The partial test results of the work discipline variable have a positive and significant effect on employee performance variables with a significance value of f<α (0.000<0.05). The results of partial testing of work environment variables have a positive and significant effect on employee performance variables with a significance value of f<α (0.000<0.05).